Simulated computed tomography-guided stereotactic adaptive radiotherapy (CT-STAR) for the treatment of locally advanced pancreatic cancer. (October 2022) - Schiff, Joshua P.; Price, Alex T.; Stowe, Hayley B.; Laugeman, Eric; Chin, Re-I; Hatscher, Casey; Pryser, Eleanor; Cai, Bin; Hugo, Geoffrey D.; Kim, Hyun; Badiyan, Shahed N.; Robinson, Clifford G.; et al.
Highlights: CT-STAR met all constraints in 98% of fractions. Simulated treatment with non-adapted plans would have yielded 94 OAR violations. 100% of non-adapted plans generated had ≥1 OAR hard constraint violation. Median time per fraction was 36.28 minutes (27.57–55.86). CT-STAR is a feasible modality for ablating locally advanced pancreatic cancer. Abstract: Background and purpose: We conducted a prospective, in silico imaging clinical trial to evaluate the feasibility and potential dosimetric benefits of computed tomography-guided stereotactic adaptive radiotherapy (CT-STAR) for the treatment of locally advanced pancreatic cancer (LAPC). Materials and methods: Eight patients with LAPC received five additional CBCTs on the ETHOS system before or after their standard of care radiotherapy treatment. Initial plans were created based on their initial simulation anatomy (PI ) and emulated adaptive plans were created based on their anatomy-of-the-day (PA ). The prescription was 50 Gy/5 fractions. Plans were created under a strict isotoxicity approach, in which organ-at-risk (OAR) constraints were prioritized over planning target volume coverage. The PI was evaluated on the patient's anatomy-of-the-day, compared to the daily PA, and the superior plan was selected. Feasibility was defined as successful completion of the workflow in compliance with strict OAR constraints in ≥80% of fractions. Results: CT-STAR was feasible in silico for LAPC and improved OAR and/or target dosimetry in 100% of fractions. Use of the PI based on the patient's anatomy-of-the-day would have yielded a total of 94 OAR constraint violations and ≥1 hard constraint violation in 40/40 fractions. In contrast, 39/40 PA met all OAR constraints. In one fraction, the PA minimally exceeded the large bowel constraint, although dosimetrically improved compared to the PI . Total workflow time per fraction was 36.28 minutes (27.57–55.86). Conclusion: CT-STAR for the treatment of LAPC cancer proved feasible and was dosimetrically superior to non-adapted CT-stereotactic body radiotherapy.